Coaching Studies Morals in Conservation Efforts Environment Sustainable Living (Case Study in Schools River Ciliwung Srengseng Sawah Jakarta) - Faisal, Juwito; Sauri, Sofyan; Tanjung, Hendri; Ibdalsyah, Ibdalsyah (Newinera Publisher, 2023)
This research is research that uses a qualitative research paradigm using descriptive qualitative methods, where data collection is carried out through observation, interviews and documentation. The purpose of this study is to know the steps taken in setting goals, planning, implementing and evaluating moral development on the environment carried out at the Ciliwung River School Srengseng Rice Fields, Jakarta. This research method is with in-depth interviews, documentation, and observation. Data analysis techniques with correlation techniques and data validity techniques with source and method triangulation techniques. The results of this study concluded that the form of implementing moral education values towards the environment to students is carried out through learning and non-learning has been running very well. The role of school coaches and teachers as mentors for activities in implementing the values of moral education in the environment for students of Ciliwung River School Srengseng Sawah Jakarta and the surrounding community have been going well. The implementation process is through the four roles of school coaches, scholars, and teachers as activity mentors as educators, motivators, and facilitators, and evaluators in the learning process and daily activities in the classroom and outside the classroom.